2021
DOI: 10.3390/su132212605
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Property Development around High-Speed Railway Stations through Land Value Capture: Case Studies in Shenzhen and Hong Kong

Abstract: Property development around transit stations has been viewed by many governments as a considerable way of financing public transportation. However, despite mounting evidence of the positive relationship between transport investment and proximate land value, the stakeholder relationship in enabling complex property–transit development has received relatively scarce attention. In this study, we analyze the railway financing strategies in two cities (Shenzhen and Hong Kong) connected by the first cross-border hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Literature reveals that the main challenges of all these programmes are the funding that nega vely impacts infrastructure development in SA. Gong et al (2021) emphasize that conven onal revenue resources seem inadequate to respond to the increasing need to provide infrastructure in different economies, Gong et al (2021) findings reinforce the importance of having alterna ve funding models such as LVC.…”
Section: Tradi Onal Methods Of Funding Infrastructure Investmentmentioning
confidence: 83%
See 2 more Smart Citations
“…Literature reveals that the main challenges of all these programmes are the funding that nega vely impacts infrastructure development in SA. Gong et al (2021) emphasize that conven onal revenue resources seem inadequate to respond to the increasing need to provide infrastructure in different economies, Gong et al (2021) findings reinforce the importance of having alterna ve funding models such as LVC.…”
Section: Tradi Onal Methods Of Funding Infrastructure Investmentmentioning
confidence: 83%
“…This concept is similar to Tax Increment Financing (TIF) by which approved development companies use the concept of 'value capture' to redevelop deteriorated neighbourhoods (Squires and Hutchison, 2014). Gong et al (2021) state that value created can be determined by linking land value increment with ini al investments, and the difference is the capital gains derived from public improvements. Infrastructure gives the most percep ble and tangible benefits to its users, it can be translated as value created.…”
Section: Planning Gain Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results correspond with actual topics involved in the interdisciplinary field of sustainable urban planning and transport development. Significantly, connection with heuristics used in analyses of transportation and railway systems [64,65] occurred. This aspect shows the potential of the proposed algorithm and methodology to be developed in other studies not only connected with railway systems and not only in transportation engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that transport infrastructure exerted a positive impact on land values; this is especially true for properties in close proximity to stations [10]. ´However, in some instances, urban transit projects could also produce negative impacts on land value usually as a result of factors such as noise, pollution or a rise in incidence of crime [21]. Analysts interested in the interaction between transport infrastructure and land value argue that areas serviced by transport infrastructure have a competitive advantage over other areas because of greater accessibility.…”
Section: The Impact Of Road Infrastructure Development On Land Value ...mentioning
confidence: 99%